Propp morphological analysis on Ready Player One novel: An attempt at defining sci-fi fiction - Emil Eka Putra (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2022)
As a genre, science fiction is still in its defining stage. This happens because of the nature of science fiction which adopts story outlines from other fiction subgenres. The adoption of this story outline result in wide variations of stories that are considered as science fiction. In the midst of this wide variety of science fiction, the question of whether science fiction has its own narrative is one of the questions that arise in the discussion of defining science fiction as a genre. This study is aimed at providing additional discourse at defining science fiction, especially discourse related to this question and identifying the relationship between fairy tales and science fiction. The study was conducted on the narrative structure of the science fiction novel Ready Player One (RPO). The study was conducted using the Propp’s fairy tale morphology theory. By adapting the method used by Propp in mapping the morphology of Russian folk tales, the functional structure of the RPO story is extracted, classified by its moves and arranged in a story scheme. The result of the analysis on the one hand shows that structurally there is no peculiarity of the narrative structure of RPO, excepts the exchange of sequences of several functions. On the other hand, this reveals the similarities in the narrative structure between fairy tales and science fiction RPO which is then interpreted as a form of connection between fairy tales and RPO as a science fiction.